Lumberjacks and hoodrats: negotiating subject positions of lesbian representation in two South African television programmes - Donaldson, Natalie (Rhodes University, Faculty of Humanities, Department of Psychology, 2011)
With the inclusion of sexual orientation in the Equality clause of the post-Apartheid constitution which demands equal rights and protection for all individuals regardless of sexual orientation, South Africa has been praised as one of the most liberal countries in the world. Because of this legal equality, gay and lesbian experiences have become a lot more visible in every day South African lives. This includes visibility in South African television programmes and film. Today, a number of South African produced television programmes have included at least one lesbian character in their storyline and many LGBTIQ activist organisations have deemed this increased visibility as a positive step for LGBTIQ rights. However, discriminatory discourses such as same-sex sexualities as 'un-African ' and unnatural, which often result in brutal hate crimes against LGBTIQ individuals (such as corrective rape), contribute to the social and cultural intolerance of same-sex sexualities. South African research into the lives of lesbian women has often related lesbian experience to that of gay men or has focused on lesbian women as victims of corrective rape and oppressive practices at the hands of the dominant heteronormative culture. This research was a discursive reception study, using three focus group discussions with self-identified lesbian audiences (black and white). The study explored how this audience received (interpreted/talked about) the available fictional representations of 'black' lesbian women and 'white' lesbian women in three clips from two South African television programmes, Society and The Mating Game. Using Wetherell's (1998) critical discursive psychology approach, this research focused on examining the 1) Subject positions made available in/by these representations; 2) Interpretive repertoires used by the audience in appropriating and/or negotiating and/or reSisting these subject positions; and 3) Ideological dilemmas experienced by participants in this negotiation process. The predominant subject positions made available in these representations were differentiated according to binary racial categories of white lesbian women and black lesbian women. For example, participants positioned white lesbian women as "lumberjacks" and "tomboys" while black lesbian women were positioned as "township lesbians" and "hood rats". In working with these subject positions, participants drew on interpretative repertoires of othering and otherness as well as interpretative repertoires of survival. In negotiating with these subject positions and others found in the discussions, ideological dilemmas often arose when participants found themselves having to draw on interpretative repertoires which extend from a heteronormative discourse. These kinds of interpretative repertoires included religion, nature, and compromise which contradicted and created a troubled position when used in relation to the participants' lesbian sexualities. Therefore, when the ideological dilemma and troubled position became apparent, participants had to work to repair the troubled position by justifying their use of these heteronormative interpretative repertoires.
Keywords: Lesbianism on television -- Research -- South Africa; Lesbians -- Research -- South Africa; Gay rights -- Research -- South Africa; Television actors and actresses -- Research -- South Africa